The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/os.12329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Unilateral Tourniquet Used in Patients Undergoing Simultaneous Bilateral Total Knee Arthroplasty

Abstract: Tourniquet use in bilateral TKA can reduce intraoperative time but was associated with a higher incidence of wound complications and larger postoperative knee swelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 25 publications
(28 reference statements)
2
29
1
2
Order By: Relevance
“…It is known that short-duration tourniquet use would result in faster recovery and less pain during the early rehabilitation period following TKA. 16 18 In the present trial, the short-duration tourniquet group was associated with better clinical outcomes, less pain, and reduced limb swelling during the early stage of rehabilitation (Figure 4). Similar results were reported by Zhang et al 19 and Ejaz et al 20 A possible explanation is that longer tourniquet use results in more pronounced oxidative stress, inflammatory response, and tissue necrosis.…”
Section: Discussionmentioning
confidence: 57%
“…It is known that short-duration tourniquet use would result in faster recovery and less pain during the early rehabilitation period following TKA. 16 18 In the present trial, the short-duration tourniquet group was associated with better clinical outcomes, less pain, and reduced limb swelling during the early stage of rehabilitation (Figure 4). Similar results were reported by Zhang et al 19 and Ejaz et al 20 A possible explanation is that longer tourniquet use results in more pronounced oxidative stress, inflammatory response, and tissue necrosis.…”
Section: Discussionmentioning
confidence: 57%
“…Four studies (n = 425) reported three-month scores. 16 , 21 , 38 , 54 The standardized mean difference between the two groups was 0.64 lower in the tourniquet group (95% CI -1.52 to 0.52) compared to the group without a tourniquet. Five studies (n = 611) participants reported 12 month scores.…”
Section: Resultsmentioning
confidence: 85%
“…Da die Studien verschiedene Einnahmezeitpunkte oder Arten der Morphinapplikation beschrieben, konnte keine Analyse durchgeführt werden. Zwei andere Studien (n = 178) untersuchten die Kniegelenkfunktion anhand des KSS [22,23]. Die Analyse zeigte, dass nach 3 Monaten postoperativ kein signifikanter Unterschied bestand (Heterogenität über 75 %; ▶ Abb.…”
Section: Analgetikabedarfunclassified